MENINGKATKAN KETERAMPILAN MENULIS KARANGAN NARASI PADA PENERAPAN METODE PEMBELAJARAN PICTORIAL RIDDLE PADA SISWA SEKOLAH DASAR - Rahma, Mega; Hana Pebriana, Putri; Aprinawati, Iis; Fitra Surya, Yenni; Fadhilaturrahmi, Fadhilaturrahmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low level of narrative essay writing skills of fifth grade students at SD TI 030 Batu Belah. The aim of this research is to improve the narrative essay writing skills of fifth grade students using the Pictorial Riddle method. This type of research is classroom action research (PTK) carried out in two cycles and each cycle consists of two meetings. The subjects of this research were class V, totaling 25 people. This data collection technique is in the form of documentation, observation and tests. Based on the results of this research, it was concluded that by applying the pictorial riddle method, it was possible to improve the skills of writing narrative essays from pre-action data which obtained a completion percentage of 28% with an average of 55.2, increasing in the first cycle of the first meeting with a student completion percentage of 36% with an average value of an average of 58.8 and in cycle I, meeting II, the percentage of completion was 48% with an average value of 64.2. Meanwhile, in cycle II, meeting I experienced an increase with a completion percentage of 72% with an average value of 73.6 and in cycle II, meeting II experienced a very good increase with a completion percentage of 88% with an average value of 82.6.